Maximizing the hydrogen content for methanol steam reforming processes by using the novel pareto-based multi-objective evolutionary algorithms - Agbulut, Umit; Bakir, Huseyin; Mo, Hao Jie; Vozka, Petr (PERGAMON-ELSEVIER SCIENCE LTD, 2024)
This research focuses on the methanol-steam reforming (MSR) process to produce hydrogen-rich syngas. A thermodynamic equilibrium reactor was designed for the process, using the Peng-Robinson fluid package for all liquid and gas components. This research aims to reveal the collective impacts of three main parameters-reaction temperature (RT) (100-500 degrees C in 50 degrees C intervals), reactor pressure (RP) (1-7 atm in 2 atm intervals), and methanol-to-water (MtW) molar ratio (0.25, 0.5, 1, 2, and 4 atm)-on syngas composition. Additionally, Pareto-based multi-objective evolutionary algorithms (MOEAs), including Multimodal Multi-Objective Differential Evolution with Improved Crowding Distance (MMODE_ICD), Multi-Objective Slime Mould Algorithm (MOSMA), and Improved Multi-Objective Manta-Ray Foraging Optimization (IMOMRFO), were used to maximize hydrogen composition at the reactor outlet. Using these algorithms, the operating parameters for the MSR were optimized. The highest hydrogen content achieved under these conditions was 67.90% among syngases. However, it could be increased by 7.22% with MMODE_ICD, 6.92% with MOSMA, and 4.71% with IMOMRFO algorithms. Furthermore, the algorithms predicted actual data with error margins of 1.1% for MMODE_ICD, 0.28% for MOSMA, and 3.52% for IMOMRFO. In conclusion, this research demonstrates that Pareto-based multiobjective evolutionary algorithms are very effective tools for increasing hydrogen production in MSR processes.
Keywords: Hydrogen-rich gas; Methanol steam reforming; Syngas composition; Parameter optimization; Pareto-based MOEAs; ENERGY; OPTIMIZATION; Chemistry; Electrochemistry; Energy & Fuels